Desain Bahan Ajar Mata Kuliah Pendidikan Agama Islam dengan Pendekatan Integratif-Interkonektif antara Religious Studies, Natural Sciences, Social Sciences, dan Humanities - Yusuf Hanafi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2016)
Dicotomy differentiation between religious and general studies affected islamic studies become stiff and rigid. So it is less responsive to the challenge and demand of developing era. This research is aimed to arrange a new handbook of Islamic education which is spirited by ethos and breath of reintegrative epistemology between religious studies and general studies, such as: natural sciences, social sciences, and humanities. Meanwhile the result targeted of this research is: (1) a new islamic education syllabus which is balance with principals of islamic studies through integrative-interconnective approach (interdisciplinary); (2) A new islamic education handbook with integrative-interconnective approach which is accepted both theoretically and practically; (3) The design of Islamic education’s teaching plan in one semester presented in 16 meetings which is tested in teaching and learning process; (4) Islamic education’s teaching scenario through a new teaching material which is able to implement the mission of islamic studies interdisciplinarily.